Spatially interpolated PM2.5 concentrations for the US for 2021 - Ford, Bonne; O'Dell, Katelyn; Fischer, Emily V.; Pierce, Jeffrey R. (Colorado State University. Libraries, 2022)
This dataset contains spatially interpolated daily PM2.5 concentrations observed by monitors in the Environmental Protection Agency's Air Quality System and non-smoke seasonal background PM2.5 estimates for 2021. It is a continuation of the previous datasets: https://doi.org/10.25675/10217/230602 and http://doi.org/10.25675/10217/233962.
This dataset contains spatially interpolated daily PM2.5 concentrations observed by monitors in the Environmental Protection Agency's Air Quality System and non-smoke seasonal background PM2.5 estimates as in https://doi.org/10.25675/10217/230602 (and http://doi.org/10.25675/10217/233962) but extended for 2021. See the readme file for details on data processing and recommended usage.
Department of Atmospheric Science